Productivity Loss Due to Deaths Caused by Cardiovascular Diseases Associated with Exposure to Air Pollutants in Sorocaba, Brazil in the Years of 2015 to 2017 - DA COSTA, Pedro Rachid; NASCIMENTO, Luiz Fernando C. (Journal of Environmental Management and Tourism; Vol 13 No 1 (2022): JEMT, Volume XIII, Issue 1(57), Spring 2022DO - 10.14505/jemt.v13.1(57).13, 2022)
Air pollution from air pollutants has associations with causes of hospitalization. Objective is to evidence the association between exposure to pollutants 0 3 , PM 10 and NO 2 , on hospital deaths in the public network. The loss of productive potential of this population was analyzed with “Anos Potencias de Vida Perdidos (APVP)”. Methodology used ecological study of the time series, where the dependent variable considered was the number of hospital admissions that died: cardiovascular diseases (41 to 64 years old). The statistical approach used the Poisson Regression model with lags from 0 to 7 days. The financial costs and increases in the number of hospitalizations resulting from increases in the concentration of 10 μg in air were estimated. Coefficients were converted into relative risk of hospitalization adopting alpha = 5%. The result was 232 occurrences, not all exclusive and related to pollution. The value obtained was R$626 thousand and a cost of use of R$319 thousand reais. The APVP, was 2547 years with an associated cost of around R$56 million. Attributing loss of life associated with pollutants in the air, due to an increase of 10 μg in the air, we could avoid 20 deaths and the cost of around 3 million reais.